How is Political Privacy Different from Personal Privacy? An Argument from Democratic Governance (Diametros, 2021)
In this paper I discuss the political value of the right to privacy. The classical accounts of privacy do not differentiate between privacy as the right of a citizen against other citizens vs. the right to privacy as the right against the state or the government. I shall argue that this distinction should be made, since the new context of the privacy debate has surpassed the historical frames in which the intelligence methods used by governments were comparable to those available to individuals. I also present cases in which political privacy serves as an instrument of protecting important collective agendas exceeding the context of personal privacy. I argue that due to its function, political privacy should be considered a necessary element of democratic governance with the rule of law, imposing legal bounds on governments’ discretionary actions.
Keywords: privacy; the right to privacy; democracy; rule of law; democratic governance; political privacy